2016
DOI: 10.1111/ijd.13350
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of six types of adverse cutaneous drug reactions using granulysin expression

Abstract: We detailed further about the histopathology of DRESS. Granulysin expression was observed in all CADR with a marked overlap of expression pattern between the six types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…We found a nonsignificant association between dermal infiltrates without epidermal alterations and viral MPEs, whereas the most consistent features of drug‐induced MPEs were epidermal changes. However, as previously reported, we confirmed the lack of a specific histopathological feature of MPEs, although some features may suggest the aetiology …”
Section: Discussionsupporting
confidence: 91%
“…We found a nonsignificant association between dermal infiltrates without epidermal alterations and viral MPEs, whereas the most consistent features of drug‐induced MPEs were epidermal changes. However, as previously reported, we confirmed the lack of a specific histopathological feature of MPEs, although some features may suggest the aetiology …”
Section: Discussionsupporting
confidence: 91%
“…To examine whether CTLs are involved in the pathogenesis of dapsone SCAR, we first detected the granulysin level (a specific cytotoxic protein of SJS/TEN [Chung et al, 2008;Wang CW et al, 2013] and DRESS [Weinborn et al, 2016], mainly released from CTLs) in the plasma of dapsone DRESS patients. (Figure 1a).…”
Section: Plasma Granulysin Level and In Vitro Lymphocyte Activation Tmentioning
confidence: 99%
“…However clinical pattern seen in their study was mainly papular scaly eczema and erythema multiforme with most frequently involved drug being captopril 15 . A study conducted by Weyers et al, in which authors examined 300 consecutive cases 16 and a study conducted by Weinborn et al, in which authors examined 106 slides 17 retrospectively, authors concluded that there was marked overlap of histological features. Thus it is often difficult to attach individual cases to one of the set of patterns.…”
Section: Fig 1: Clinical Pattern Of Cadrs Fig 2: Drug Class and Sevmentioning
confidence: 99%